Ways to improve the competitiveness of butter producers in the context of import substitution - Rassulova, A.; Umyrzakova, A. (BUKETOV BUSINESS REVIEW, 2021)
Object: This article displays the statistical data of the EAEU countries, where the share of imports of dairy products from Kazakhstan is indicated. An explanation of the criteria by which consumers of dairy products consume products from an imported manufacturer, and by what criteria from a domestic manufacturer, is given. Methods: methodology and approach used are statistical data, qualitative method, namely questionnaire. Findings: The theoretical value, to find the features of domestic enterprises, to consider the competitive, economic factors of the enterprise. Through quantitative and qualitative research (structured interviews), we can consider the need to study consumer tastes and replace them with domestic products. Conclusions: according to the results of a survey among consumers of butter, it turned out that the majority of consumers are guided by such criteria as quality, naturalness of ingredients, as well as pricing policy when choosing butter. In order for the company to be competitive in the food industry market, it is necessary to pay special attention to product quality, since this directly affects the choice of the consumer.